Plastic instability and fracture of ultra-thin stainless-steel sheet. (1st October 2020) - Zhang, Peng; Pereira, Michael P.; Abeyrathna, Buddhika; Rolfe, Bernard F.; Wilkosz, Daniel E.; Hodgson, Peter; Weiss, Matthias
Abstract: A new approach was used to characterise the hardening, instability and fracture behaviour of ultra-thin (0.1 mm) stainless steel sheets under stress triaxiality ranging from 0.37 to 0.66. The Swift and the linear hardening laws were used to capture the stress–strain relationship for the complete level of plastic deformation that exceeds that achievable by a uniaxial tensile test. For this, the Virtual Field Method (VFM) was applied, which uses the strain field measured on the surface of the notched samples, to output the material hardening parameters. To determine one set of hardening parameters that fits all conditions of stress triaxiality, an upper bound of major strain was selected for the VFM fitting that optimises a single set of hardening parameters across all of the stress triaxiality conditions. The void coalescence parameter in a Gurson-Tvergaard-Needleman (GTN) fracture model was calibrated and the model results for fracture initiation were validated experimentally with a quasi-biaxial stretching test.